O transtorno de déficit de atenção e hiperatividade e auto organização - Camilo, Lujani Aparecida; Pereira Júnior, Alfredo [UNESP] (My University, 2014)
Attention Deficit Hyperctivity Disorder is one of the main reasons for seeking outpatient mental health of children and adolescents. Thus, referral to health services for children with learning difficulties in school or behavior problems have been very common. Many of these referrals made by a school complaint aim that any disease, disorder or disability that prevents the child from learning to be identified. The purpose of this article is to reflect on the concept of ADHD, wich can be fully resignified when taken by biopsychosocial explanatory model, because the disease does not become the sole focus and other factors (social, psychological, physiological) present and contribute equally to the increase or decrease of the disorder. As well as studies of Self Organization can contribute to a more comprehensive view of the health-disease process.

O Transtorno de Déficit de Atenção/Hiperatividade é uma das principais causas de procura de ambulatório de saúde mental de crianças e adolescentes. Assim, o encaminhamento para os serviços de saúde em crianças com dificuldades de aprendizagem escolar ou com problemas de comportamento tem sido freqüente. Muitos desses encaminhamentos realizados por uma queixa escolar têm como objetivo de que seja identificado alguma doença, distúrbio ou deficiência que impede a criança de aprender. O objetivo desse artigo é fazer refletir sobre o conceito de TDAH, o qual pode ser totalmente resignificado quando tomado pelo modelo explicativo biospsicossocial, pois a doença não torna-se o único foco e os demais fatores (sociais, psicológicos, fisiológicos) apresentam e contribuem equitativamente para o aumento ou diminuição do transtorno. Assim como os estudos de Auto Organização podem contribuir para uma visão mais abrangente do processo saúde-doença.
Attention deficit hyperactivity disorder and self organization
Keywords: ADHD; Self Organization; Biopsychosocial; TDAH; Auto Organização; Biopsicossocial